Is there really a Global Business Cycle? A Dynamic Factor Model with Stochastic Factor Selection - Tino Berger; Lorenzo Pozzi (Tinbergen Institute, 2016)
We investigate the presence of international business cycles in macroeconomic aggregates (output, consumption, investment) using a panel of 60 countries over the period 1961 - 2014. The paper presents a Bayesian stochastic factor selection approach for dynamic factor models with predetermined factors. The literature has so far ignored model uncertainty in these models as common factors (i.e., global, regional or otherwise) are typically imposed but not tested for. We focus in particular on the existence of a global business cycle as the literature has, in our opinion unjustifiably, taken for granted its existence. In contrast to the literature, we find no evidence to support its presence.
Keywords: C52; C32; F44; 330; Global business cycle; dynamic factor model; Bayesian; model selection